1981
DOI: 10.1017/s1742758400002125
|View full text |Cite
|
Sign up to set email alerts
|

Shootfly species and their graminaceous hosts in Andhra Pradesh, India

Abstract: Intmat~ond Crop Reuuch lnsulute lor the Semi-Arid Tropn (ICRISAT) Patancheru. PO.. 542 324 A P. India A*mct-Thu p a w d m b n the results ofeatennve runng of shoolHy s p c~n of the genera 4rher1-OM and 4cr1rorhana from cult~valcd and w~ld Grrnuneae ln Andhra Pradnh. lnd~a N~nctun lly specla werc recorded from 41 gramlnrcmw s p c l n ~nclud~ng cult~vated sorghum 4rhrngena nxcors an Important pest of sorghums in the Old World troptcl. w u reared from ! ? host plants Only culuvated and wtld spma of wrghum were Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…His team's findings were published in the Arkiv för Zoologi where Villeneuve noted that the species appeared to be an undescribed member of the genus Atherigona (Villeneuve, 1936). During the late 21st century, various entomological researchers have found evidence of adult A. reversura throughout Southeast Asia while they were investigating other Atherigona species, such as the closely‐related sorghum shoot fly, A. soccata (Davies and Seshu Reddy, 1981; Pont, 1981; Pont and Magpayo, 1995). Generally speaking, the BSM appears to be more common in warm, humid climates.…”
Section: Initial Discovery Through Invasion To the United Statesmentioning
confidence: 99%
“…His team's findings were published in the Arkiv för Zoologi where Villeneuve noted that the species appeared to be an undescribed member of the genus Atherigona (Villeneuve, 1936). During the late 21st century, various entomological researchers have found evidence of adult A. reversura throughout Southeast Asia while they were investigating other Atherigona species, such as the closely‐related sorghum shoot fly, A. soccata (Davies and Seshu Reddy, 1981; Pont, 1981; Pont and Magpayo, 1995). Generally speaking, the BSM appears to be more common in warm, humid climates.…”
Section: Initial Discovery Through Invasion To the United Statesmentioning
confidence: 99%
“…ve S. halepense' dir (Şekil.3). Konukçuları arasında Sorghum spp., Echinochloa colonum, E. procera, Cymbopogon sp., Paspalum scrobiculatum, Pennisetum glaucum (Malipatil & Plant Health Australia, 2008) ve Brachiaria, Cynodon, Echinochloa, Eragrostis, Panicum, Pennisetum, Setaria, Sorghum cinslerine ait türlerin yanında hububat bitkilerinden buğday ve mısırda da gelişmesini sürdürebileceği bildirilmiştir (Davis & Seshu Reddy, 1981;Gahukar, 1991).…”
Section: Tanımı Ve Konukçularıunclassified
“…Except for a few reports of the insect surviving the offseason on wild hosts (Starks, 1970;Granados, 1972;Davies and Seshu Reddy, 1981;Delobel and Unnithan, 1981) and on tillers produced by sorghum stubble after harvest (Delobel and Unnithan, 1981), it is still a subject of speculation. It has been suggested that A. soccata larvae and/or pupae undergo a quiescent period or aestivationdiapause during the off-season, thus surviving until the next crop (Barry, 1972;Clearwater and Othieno, 1977;Ogwaro, 1979).…”
Section: Introductionmentioning
confidence: 99%